Glycosaminoglycans and fucoidan have a protective effect on experimental glomerulonephritis - Buijsers, Baranca; Maciej-Hulme, Marissa; Jacobs, Maaike; Bebber, Marinka Bakker-van; de Graaf, Mark; Salmenov, Rustem; Parr, Naomi; Rabelink, Ton J.; Nijenhuis, Tom; van der Vlag, Johan (Frontiers in Molecular Biosciences, 2023)
The glomerular endothelial glycocalyx is degraded during inflammation. The glycocalyx plays a pivotal role in endothelial function and is involved in many processes including binding of chemokines and cytokines, leukocyte trafficking, and preventing proteinuria. HS-based therapeutics are a promising novel class of anti-inflammatory drugs to restore a compromised endothelial glycocalyx under inflammatory conditions. Recently, we demonstrated that treatment with HS extracted from unstimulated glomerular endothelial glycocalyx (unstimulated HSglx) reduced albuminuria during anti-GBM induced glomerulonephritis. Since endothelial HS domains are distinct in unstimulated versus inflammatory conditions, we hypothesized that 1) unstimulated HSglx, 2) LPS-stimulated HSglx, 3) the HS-mimetic fucoidan and 4) the glycosaminoglycan preparation sulodexide, which is a mixture of low molecular weight heparin and dermatan sulfate, might have different beneficial effects in experimental glomerulonephritis. The effect of unstimulated HSglx, LPS HSglx, Laminaria japonica fucoidan, or sulodexide on experimental glomerulonephritis was tested in LPS-induced glomerulonephritis in mice. Analyses included urinary albumin creatinine measurement, cytokine expression in plasma and renal cortex, and renal influx of immune cells determined by flow cytometry and immunofluorescence staining. Furthermore, the observed in vivo effects were evaluated in cultured glomerular endothelial cells and peripheral blood mononuclear cells by measuring cytokine and ICAM-1 expression levels. The ability of the compounds to inhibit heparanase activity was assessed in a heparanase activity assay. Treatment of mice with LPS HSglx or sulodexide near-significantly attenuated LPS-induced proteinuria. All treatments reduced plasma MCP-1 levels, whereas only fucoidan reduced IL-6 and IL-10 plasma levels. Moreover, all treatments reversed cortical ICAM-1 mRNA expression and both fucoidan and sulodexide reversed cortical IL-6 and nephrin mRNA expression. Sulodexide decreased renal influx of CD45+ immune cells whereas renal influx of macrophages and granulocytes remained unaltered for all treatments. Although all compounds inhibited HPSE activity, fucoidan and sulodexide were the most potent inhibitors. Notably, fucoidan and sulodexide decreased LPS-induced mRNA expression of ICAM-1 and IL-6 by cultured glomerular endothelial cells. Our data show a potentially protective effect of glycosaminoglycans and fucoidan in experimental glomerulonephritis. Future research should be aimed at the further identification of defined HS structures that have therapeutic potential in the treatment of glomerular diseases.